A study on adverse obstetric outcome and it’s relation with antenatal psychosocial stress - Jayachandran, Sija Chandran Lisa; Brahmanandan, Mayadevi; Nambisan, Bindu; Salmabeevi, Shaila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Antenatal psychosocial stress is a common condition, perhaps more prevalent than gesational diabetes. High ante-partum stress levels are associated with adverse pregnancy outcomes. Data related to psychosocial stress and pregnancy outcomes are very much limited in our country. The objective of the study was to study the obstetric and perinatal outcome in patients with psychosocial stress and to determine the association between socio demographic factors and psychosocial stress in antenatal period. Methods: Using a 10 item stress scale (which was validated and developed at SAT hospital, Government Medical College, Thiruvananthapuram) 153 antenatal women who satisfied the inclusion criteria and attending the outpatient department (OPD) were evaluated and followed up until delivery and their findings noted. Results: The average stress scores among mild stress group, moderate and severe stress group were 6.31, 9.18, 14.82 respectively. 23.5% of mild stress group, 23.5% of moderate stress group and 51% of severe stress group had preterm delivery. There was significant association between incidence of preterm labour and stress levels. Incidence of preterm delivery was high in severe stress group (p<0.05). Caesarean section rate was found to be high in patients with increased stress levels. 29.4% of mild stress group, 47.1% of moderate stress group and 60.8% of severe stress group were caesarean sections. Babies of high stress score mothers did not cry soon after birth and the association was significant. There was no statistical significance between socio-demographic factors and stress. Furthermore, no significant association was noted between stress levels and duration of hospital stay, history of complications in previous pregnancy, obstetric complications in present pregnancy, birth weight, neonatal deaths, maternal age, place of residence, education, income and family type. Conclusions: As psychiatric problems during antenatal period and postnatal period are increasing the world over, identification of women at risk and specific interventions targeted to reduce psychosocial stress will improve feto-maternal outcomes. Hence stress assessment and appropriate interventions like physical relaxation, meditation, counseling and providing social support services should be integrated to routine antenatal care.